The relationship between bizygomatic width and mesiodistal width of six maxillary anterior teeth in a Javanese population - Indrastuti, Murti; Barunawati, Sri Budi; Hasudungan, Dian Samuel (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
The selection of the mesiodistal width of maxillary anterior teeth is the key to success in prosthodontic treatment. Determining anterior teeth width when there is no existing pre-extraction record can be done through bizygomatic width measurement. The purpose of this study was to look at the relationship between bizygomatic width and mesiodistal width of six maxillary anterior teeth in the Javanese population. This study used a cross-sectional design and was conducted on 32 Javanese subjects who met the following criteria: being 18-25 years of age, having Angle class 1 malocclusion, having complete maxillary anterior permanent teeth, not using dentures, currently not undergoing any orthodontic treatment, and having no abnormalities found in the facial area. The bizygomatic width was measured with a digital caliper with an accuracy of 0.01 mm from the marked right and left bizygomatic points. The mesiodistal width of the six maxillary anterior teeth was measured using dental floss looped from the distal left canine to the right canine. Dental floss marked with a pen was stretched horizontally on paper and then measured with a digital caliper with an accuracy of 0.01 mm. The measurement was done in triplicate. Data were analyzed using Pearson’s correlation and the simple linear regression test. This study’s analysis revealed a strong and positive correlation (r = 0.538 and p < 0.05) between the bizygomatic width and mesiodistal width of the maxillary anterior teeth. The result of the simple linear regression test showed a significant result (p < 0.05). It can be concluded that there was a relationship between the bizygomatic width and the mesiodistal width of the six maxillary anterior teeth in the Javanese population. The mesiodistal width of the six maxillary anterior teeth in the Javanese population can be measured by multiplying the bizygomatic width by the multiplier factor, i.e., 0.427.